Review: Fusion fault tolerance replication model and fragmentation in grid-cloud distributed environments - Kunna Azrag, Mohammed Adam; Noraziah, Ahmad; Nurzety Aqtar, Ahmad Azuan; Zarina Mohamad, Zarina; Odili, Julius Beneoluchi (Science Publications, 2025)
The study investigates key aspects of data management in distributed systems, focusing on fragmentation, replication and fault tolerance. With the increasing complexity of modern applications, efficient data handling across multiple nodes has become critical. The study begins by reviewing existing literature and moves on to analyze fragmentation techniques, evaluating their role in optimizing performance and resource utilization. Replication methods are discussed next, highlighting how data duplication improves availability and resilience against failures. The results indicate that efficient data management techniques in distributed systems significantly improve performance, availability and reliability. These findings contribute to a deeper understanding of the challenges and opportunities in distributed system environments, offering valuable insights for researchers and practitioners.